Thermotolerance of early life stages of the golden kelp Laminaria ochroleuca - GATTOLIN, CLAUDIA (2024)
open Kelps, classified under the order Laminariales, are brown seaweeds which can be found along all coastlines of the world – except Antarctica. These organisms play a crucial role as “ecosystem engineers” for their ability to form marine forests, three-dimensional, complex, heterogeneous and highly productive habitats which can host many different species: for this reason, their presence is fundamental to maintain ecosystem functions and to prevent biodiversity from declining. However, nowadays kelp forests are declining worldwide as they are affected by several anthropogenic stressors, some of them being overfishing, ocean warming and eutrophication. To counteract this decline, extensive efforts have been made by scientists and experts to restore these essential habitats. Numerous projects are being funded annually to either recreate lost forests or enhance the resilience of existing ones. Effective restoration strategies require comprehensive scientific knowledge regarding the tolerance, resistance and resilience of kelp species. However, extensive knowledge about the physiology and phenotypic plasticity of many species is now still lacking. This Master Thesis focuses on Laminaria ochroleuca, commonly known as “golden kelp”. It is a warm-temperate Iberian species belonging to the order Laminariales, found in relatively warm waters ranging from southern England to Morocco. It reproduces sexually and is characterized by a heteromorphic and diplohaplontic life cycle, which features an alternance between a microscopic haploid gametophyte and a macroscopic diploid parenchymatous sporophyte. Due to variations in sea surface temperatures and habitat depths, distinct populations of L. ochroleuca have emerged, potentially leading to intraspecific diversity and phenotypic plasticity in response to varying environmental conditions. The study aims to investigate whether different populations of L. ochroleuca exhibit adaptive differences in gametophyte reproductive success in response to temperature variations during ...